Maintenance of PKMζ-modulated synaptic efficacies despite protein turnover - Aslam, Naveed (Frontiers in Systems Biology, 2023)
How the synaptic efficacies can be maintained despite the fast turnover of proteins at synapses? Partially, we know that the synthesis of new proteins is essential for the induction of the late, long-lasting phase of LTP (L-LTP). Recent experiments suggest that the concentration of PKMζ is increased during L-LTP, and that inhibiting the PKMζ activity during the maintenance phase can effectively reverse L-LTP. Experiments have also shown that phosphorylation is necessary for the activation of PKMζ. However, it is not clear what mechanism maintains the level and activity of PKMζ despite protein turnover and phosphatase activity? Using a mathematical modeling framework, I examine the hypothesis that activity of PKMζ is sustained through a local switching mechanism. The model for the switching mechanism is motivated by several experimental observations: 1. PKMζ has two phosphorylation sites, one is mediated by another constitutively active kinase PDK1 (T410) and is essential for its activity, and another is an autophosphorylation site (T560). 2. The phosphorylation of PKMζ increases its stability i.e., the doubly phosphorylated PKMζ has a significantly longer lifetime than the unphosphorylated and singly phosphorylated states of PKMζ. 3. The doubly phosphorylated PKMζ also regulates the new synthesis of PKMζ through a translation feedback loop. I implemented, a mass action model, which is consistent with these observations. My results show that such a model can be bistable, and that L-LTP induction produces an increase in total amount of PKMζ at active synapses. The increase in PKMζ concentration is maintained through the regulation of new protein synthesis by PKMζ. My results also show that blocking the activity of PKMζ, in a dose dependent manner, can effectively abolish the increase in the total amount of PKMζ, which is consistent with the effect that the PKMζ inhibitor ZIP has experimentally. My model is consistent with available experimental results regarding phopsphorylation levels of PKMζ and the temporal aspects of blocking experiments and produces new prediction.